Determination of discrete element simulation parameters of rice milling machine - ZHANG Ning; CAO Xian-zhou; WANG Xin-yu; SUN Yan-ling (Shipin yu jixie, 2023)
Objective: To solve the problem that the roller is inconvenient to operate and the concept of rolling friction coefficient and sliding friction coefficient is confused. Methods: EDEM software was used to simulate the white milling process. Taking MNAW18 rice mill as a reference and taking Feng Liangyou series brown rice as a sample, a set of method for measuring discrete element simulation parameters of rice mill was established by independently setting up an experimental bench and combining with simulation calibration. Results: Using the self-made collision coefficient experimental device and video motion processing software, the collision recovery coefficients between brown rice and brown rice, roller and screen were 0.34, 0.24 and 0.43 respectively. Based on the relationship between inclined angle and static friction coefficient, the static friction experiment is designed. The static friction coefficients between brown rice and brown rice, roller and screen were 0.467, 0.881 and 0.550 respectively. The rolling friction coefficient was calibrated through the combination of brown rice stacking angle experiment, brown rice inclined plane rolling experiment and discrete element simulation experiment. The rolling friction coefficients between brown rice and brown rice, roller and screen were 0.013, 0.101 and 0.159 respectively. Conclusion: Through the secondary simulation, the error between the simulation results and the measured results is within a reasonable range, which indicates that the parameter calibration data is reliable.